2020
DOI: 10.3390/coatings10060516
|View full text |Cite
|
Sign up to set email alerts
|

Development of Cerium-Doped Hydroxyapatite Coatings with Antimicrobial Properties for Biomedical Applications

Abstract: Antibacterial cerium-doped hydroxyapatite (Ce-HAp) layers have been researched sparingly in recent years. The Ce-HAp powder, Ca10−xCex(PO4)6(OH)2 with xCe = 0.05, was obtained by an adapted chemical co-precipitation method at room temperature. The target was prepared using the Ce-HAp (xCe = 0.05) powder sintered in air at 600 °C. The coatings on the Ti substrate were generated in plasma using a radio frequency (RF) magnetron sputtering discharge in an Ar gas flow in a single run. To collect the most complete i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 59 publications
6
22
1
Order By: Relevance
“…These results are in good agreement with previously reported studies regarding the lack of antimicrobial properties of hydroxyapatite [20,59,60]. Moreover, previous studies [15,[56][57][58][59][60][61][62][63][64] reported that the antifungal effect of samarium could be explained by the fact that samarium ions have the ability to attach to the cell membrane leading to changes of its permeability. Furthermore, samarium ions that are released from the composite matrix could disrupt the bacterial membrane integrity thus affecting a multitude of cellular processes such like adhesion, ion conductivity and cell signaling [61].…”
Section: Resultssupporting
confidence: 93%
“…These results are in good agreement with previously reported studies regarding the lack of antimicrobial properties of hydroxyapatite [20,59,60]. Moreover, previous studies [15,[56][57][58][59][60][61][62][63][64] reported that the antifungal effect of samarium could be explained by the fact that samarium ions have the ability to attach to the cell membrane leading to changes of its permeability. Furthermore, samarium ions that are released from the composite matrix could disrupt the bacterial membrane integrity thus affecting a multitude of cellular processes such like adhesion, ion conductivity and cell signaling [61].…”
Section: Resultssupporting
confidence: 93%
“…In this context, the adding of chitosan to hydroxyapatite (in the synthesis process), for its future use as a sputtering target in rf magnetron discharge, leads to different surface morphologies of HApCs coatings (see Figure 5 a,b) in comparison with those of HAps [ 10 , 12 ]. Thus, on the surface of HApCs layers, grain-like structures with spherical shapes and various sizes are formed that can be assigned to the coagulation of macromolecules of HApCs (produced in the magnetron plasma), on the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous works, we showed that at low radio frequency (rf) working powers, in magnetron sputtering plasma discharges, bioceramic multicomponent coatings for biomedical applications can be synthetized [ 10 , 11 , 12 ]. In [ 10 ], we showed that in rf magnetron discharge at about 1.2 × 10 −2 mbarr and 50 W rf power, after 4 h deposition time, regular granular-like structures on the surface of calcium phosphate layers deposited on Ti substrates can be generated.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the obtaining of novel cerium-doped hydroxyapatite materials for the development of medical device coatings could contribute with important advances in the area of antimicrobial agents. In a previous study, we presented cerium-coated hydroxyapatite (x Ce = 0.05) coatings obtained by plasma by RF magnetron sputtering [24].…”
Section: Introductionmentioning
confidence: 99%